Women Contributions in Human Development: A Study at Women’s Shelters in Selangor - Mansor, Nurul Husna; Abd Razzak, Monika @ Munirah; Ab Rahim, Nik Mohd Zaim (Jurnal Usuluddin, 2019)
Women have occupied positions as important as men in fulfilling their roles towards the development of a nation. Evidently, women have contributed beyond their traditional domestic responsibilities as wives and mothers. Iin fact, they have been actively participated in various employment sectors, both locally and abroad. In addition, The National Women Policy has already put in place the strategic planning and approaches to empower women towards establishing well educated and trained human resources among women to contribute competitively in nation building activities. In reference to the contribution of women in various fields, this study however focuses on the contributions of women employees in dealing with issues and solving problems faced by women specifically at Baitul Ehsan and Darul Wardah, both are under the purview of the Selangor Women’s Shelter. This study is in the form of case study which utilizes qualitative approaches. The data for this study is obtained via interviews and observations on six employees who work at the centers, who are selected on objective consensual sampling basis. The study reveals that the women employees who work at the centers have played good roles in listening and dealing with the problems faced by their residents. Moreover, the employees are known to be very committed and render undivided supports towards the efforts and programs to spiritually and physically develop women who are facing problems with lives, by appropriate means.